2007
DOI: 10.1007/s00248-007-9238-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Pioneers Facilitate Phototrophic Biofilm Development

Abstract: Phototrophic biofilms are matrix-enclosed microbial communities, mainly driven by light energy. In this study, the successional changes in community composition of freshwater phototrophic biofilms growing on polycarbonate slides under different light intensities were investigated. The sequential changes in community composition during different developmental stages were examined by denaturing gradient gel electrophoresis (DGGE) of polymerase chain reaction (PCR)-amplified 16S rRNA gene fragments in conjugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 34 publications
3
51
2
Order By: Relevance
“…The fast-growing green algae, Chlorococcum, Desmodesmus and Scenedesmus, are probably responsible for the shorter lag phase in biofilms grown at higher irradiances. This confirms findings from Roeselers et al (2007) on the pioneering role of Scenedesmus attachment to polycarbonate substrata in parallel experiments on Fiumicino WWTP biofilms.…”
Section: Discussionsupporting
confidence: 88%
“…The fast-growing green algae, Chlorococcum, Desmodesmus and Scenedesmus, are probably responsible for the shorter lag phase in biofilms grown at higher irradiances. This confirms findings from Roeselers et al (2007) on the pioneering role of Scenedesmus attachment to polycarbonate substrata in parallel experiments on Fiumicino WWTP biofilms.…”
Section: Discussionsupporting
confidence: 88%
“…2a) (Ramanan et al, 2016). Roeselers et al (2007) reported that substrate precolonization by Betaproteobacteria accelerated the growth and adhesion of Microcoleus vaginatus to polycarbonate surfaces. Similarly, Park et al (2008) found that the addition of Brevundimonas sp.…”
Section: Cooperative Interactionmentioning
confidence: 99%
“…in the mid and late stages of biofilm colonization. It was likely that early colonizers changed the environmental conditions in the biofilms, and this change could facilitate the attachment of filamentous cyanobacteria (Roeselers et al, 2007). Previous studies also reported that filamentous cyanobacteria frequently prevailed in the cyanobacteria communities in low nutrient availability (Rejmankova and Komarkova, 2000) and extreme environments (Vincent et al, 1993).…”
Section: Discussionmentioning
confidence: 95%